Multifunctional curing component for epoxidized novolac resin by grafting poly (amidoamine) on carbon nanotubes using a divergent method. (10th May 2018) - Pourhosseini‐Pakdel, Zohreh; Roghani‐Mamaqani, Hossein; Azimi, Reza; Gholipour‐Mahmoudalilou, Meysam
Abstract : Poly(amidoamine)‐grafted carbon nanotube (CNTD) was synthesized and used as a multi‐component curing agent for epoxidized novolac resin (ENR). This composite and curing agent can improve thermal stability of the resin due to its tubular graphitic core and also dendritic amino‐functionalities. The ENR was cured in the presence of different amounts of CNTD. Then, the thermal degradation temperature and also char content of the products were compared with the ethylenediamine‐cured ENR. Successful functionalization of oxidized carbon nanotubes with poly(amidoamine) was evaluated by Fourier transform infrared spectroscopy, X‐ray photoelectron spectroscopy, X‐ray diffraction, and thermogravimetric analysis. According to the thermogravimetric analysis results, char content of ethylenediamine‐cured ENR is 44.7% which increased to 54.6%, 55.5%, and 56.9% by the addition of 3, 5, and 8 wt% of CNTD into the resin matrix. Also, addition of CNTD content increased thermal stability of the composites. The tubular structure of CNTD was observed by scanning and transmission electron microscopies.